Pemetaan Sistematis Trend Teknologi E-Business Untuk Sektor Logistic Dan Forwarding - Elfarosa, Ketut Vini; Dewi, Kadek Cahya; Kencanawati, AAA Mirah (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
This study aims to map research trends in the field of e-business technology for the logistics and forwarding sector. The study used a systematic mapping and systematic literature review approach. There were 3 research questions that are used as references in this study, namely: (1) What is the trend of research types on e-business technology for the logistics and forwarding sector?, (2) What is the trend of topics on e-business technology for the logistics and forwarding sector?, and (3) How is the mapping of e-business technology research for the logistics and forwarding sector based on research types and topics? The search focused on literature published in 2020-2024. The keywords are "E-business (technology OR implementation) for logistics and forwarding". The searches were carried out by reviewing the literature available in journal sources (ScienceDirect and SpringerLink). The trend of research types is dominated by research with evaluation and solution types. While the trend of research topics is dominated by artificial intelligence topics. Mapping of articles based on research types and topics has been carried out and can be used as a reference in determining further research, by filling in the gaps in topics and types of research that have not been filled.